A kompetenciák fejlesztésének lehetőségei a szervezeti kultúrán keresztül - Málovics, János; Málovics, Éva (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
We can often read in the special literature about the interaction of the organizational culture and the competences. Culture and competences are important parts of the condi-tions of the organizational success by the management literature. In our opinion the mechanism of the impact of the culture to the competences has not been discovered and not empirical proved completely yet. The aim of our research was the completion of the above mentioned lack, we researched this topic in a pilot study, of which results we present in this paper.